Dynamic Fuel Price Pass-Through : Evidence from a New Global Retail Fuel Price Database - Kpodar, Kangni (IMF Working Papers; Working Paper ;, 2016)
This paper assesses the dynamic pass-through of crude oil price shocks to retail fuel prices using a novel database on monthly retail fuel prices for 162 countries. The impulse response functions suggest that on average, a one cent increase in crude oil prices per liter translates into a 1.2 cent increase in the retail gasoline price at peak level six months after the shock. However, the estimates vary significantly across country groups, ranging from about 0.5 cent in MENA countries to two cents in advanced economies. The results also show that positive oil price shocks have a larger impact than negative price shocks on the retail gasoline price. Finally, the paper underscores the importance of the new dataset in refining estimates of the fiscal cost of incomplete pass-through.